Power and Gender: Female Perpetrators of Child Sexual Abuse from Islamic Legal Perspective - Adawiyah, Robi’atul; Habi, Nuraida Fitri; Nur, Syamsiah; Mukhlisa, Dian (Jambe Law Journal, 2026)
This study addresses the limited scholarly attention to female sexual offending in child sexual abuse, which remains under-theorized within both power relations discourse and Islamic legal studies. Existing literature predominantly frames sexual violence as male-perpetrated, leaving a gap in understanding how gender, power, and vulnerability intersect when women become perpetrators. This article examines how power operates in cases of female-perpetrated sexual abuse and how such conduct is interpreted within Islamic legal principles. Drawing on a qualitative socio-legal approach, this study combines doctrinal analysis of Islamic legal sources with an empirical case study of a child sexual abuse case in Jambi, Indonesia. The analysis is primarily informed by Foucauldian conceptions of power, particularly the interplay between knowledge, control, and dependency. The findings demonstrate that power in this context is not merely coercive but operates through subtle mechanisms of normalization, economic dependency, and psychological manipulation, enabling the perpetrator to exploit structurally vulnerable children. Furthermore, from an Islamic legal perspective, such acts constitute violations of fundamental legal objectives (maqāṣid al-sharī‘a), particularly the protection of dignity and life, and are subject to gender-neutral accountability. This study contributes to the literature by challenging gendered assumptions about sexual violence, extending the application of power relations theory to female offending, and offering a nuanced integration of socio-legal and Islamic legal analysis in understanding child sexual abuse.